Laser and electric-field driven hydrogen generation from methanol vapor - P. Wiewiórski; W. Mista; R. Tomala; M. Stefanski; T. Zhou; L. Zhang; W. Jones; W. Strek (Results in Chemistry)
The generation of hydrogen from methanol vapor was investigated under the simultaneous laser induced and electric-field ionization of methanol vapor using graphene aerogel as electrode and optical target for ejection of hot electrons. It was observed that the process of methanol conversion to hydrogen was significantly enhanced, reaching almost 90 % efficiency. The process occurred without CO2 and with low CH4 emissions.